Language Variation - European Perspectives V : Selected papers from the Seventh International Conference on Language Variation in Europe (ICLaVE 7), Trondheim, June 2013 - Torgersen, Eivind; Hårstad, Stian; Mæhlum, Brit, 1957-; Røyneland, Unn (Studies in language variation ;, 2015)
"Language Variation -- European Perspectives V is based on papers presented at the Seventh International Conference on Language Variation in Europe (ICLaVE 7), which was held in Trondheim, Norway from 26 to 28 June 2013. The 17 papers included in the book explore phonetic and phonological variation (Bitenc and Kenda-Jež; Hildenbrandt and Moosmüller; Jansen; Schaufuss; Schleef, Flynn and Ramsammy; Stuart-Smith, Rathcke, Sonderegger and Macdonald), morphology (Padilla-Moyano), syntax (Christensen and Juel Jensen; Jónsson, Brynjólfsdóttir and Sverrisdóttir), morphosyntax (Auger and Wycoff; Cerruti and Regis), language ideology, linguistic practices and language attitudes (Strand; Hall-Lew, Fairs and Lew; Dunmore and Smith-Christmas), code-switching (Amadou; Bucher) and language documentation (Kühl). The book is essential reading for scholars working on variation and change in European languages. The articles in the present volume investigate Romani, Turkish, Greek, Slovene, Picard, Swiss-German, Basque, Danish, Italian, English, Gaelic, Icelandic Sign Language, Faroe Danish and Norwegian."--